A novel hypermucoviscous Klebsiella pneumoniae ST3994-K2 clone belonging to Clonal Group 86. Issue 8 (22nd September 2021) - Cerdeira, Louise; Nakamura-Silva, Rafael; Oliveira-Silva, Mariana; Sano, Elder; Esposito, Fernanda; Fuga, Bruna; Moura, Quézia; Miranda, Carlos Eduardo Saraiva; Wyres, Kelly; Lincopan, Nilton; Pitondo-Silva, André
ABSTRACT: Emergent hypervirulent Klebsiella pneumoniae has been responsible for severe diseases, representing a serious threat to public health. We report the whole-genome sequencing of a novel ST3994-K2 clone, a single locus variant of ST86 K2, which is considered a worrying hypervirulent clone that emerged in several parts of the world. The strain K. pneumonia Kpi144 was isolated in 2013 from a blood culture of a 69-year-old male patient admitted to a tertiary hospital in Teresina, state of Piauí, northeastern Brazil. The strain was susceptible to 41 antibiotics tested, presented hypermucoviscous phenotype and a virulent behavior was observed in the Galleria mellonella infection model. Moreover, the virulome showed several virulence genes. To the best of our knowledge, this is the first worldwide report of a novel ST3994-K2 K. pneumoniae clone, an SLV of ST86 K2, which is considered a worrying virulent clone that has emerged in several parts of the world, including South America and Brazil. Abstract : This is the first worldwide report of a novel hypermucoviscous ST3994-K2 K. pneumoniae clone, an SLV of ST86 K2, which is considered a worrying virulent clone that has emerged in several parts of the world.